2004
DOI: 10.1213/01.ane.0000093309.75358.30
|View full text |Cite
|
Sign up to set email alerts
|

Levobupivacaine for Pediatric Spinal Anesthesia

Abstract: This noncomparative, descriptive study showed that levobupivacaine, the S(-)-enantiomer of bupivacaine, has equivalent clinical efficacy in spinal anesthesia in children to that of racemic bupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 10 publications
2
31
0
7
Order By: Relevance
“…The present study demonstrates that ropivacaine is an effective local anesthetic for spinal applications in children because the success rate of the block, 92%, was the same as has been reported with racemic bupivacaine (11) and levobupivacaine (13). In addition, there was only one failed spinal block with ropivacaine, similar to that with bupivacaine (11,13).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present study demonstrates that ropivacaine is an effective local anesthetic for spinal applications in children because the success rate of the block, 92%, was the same as has been reported with racemic bupivacaine (11) and levobupivacaine (13). In addition, there was only one failed spinal block with ropivacaine, similar to that with bupivacaine (11,13).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, there was only one failed spinal block with ropivacaine, similar to that with bupivacaine (11,13). However, whether ropivacaine should replace bupivacaine in intrathecal use is open for discussion.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] The clinical outcomes of levobupivacaine in children who underwent spinal anaesthesia were similar to those achieved with the same dose of bupivacaine. 25 A randomized, double-blind study of intrathecally administered 0.5% isobaric levobupivacaine or 0.5% hyperbaric bupivacaine in 70 patients scheduled to undergo elective transurethral endoscopic surgery found similar results between the two groups for the following variables: duration of sensory block, duration of two segment regression, time of onset and expiration of motor block, side effects, and pain scores at the beginning of the operation. 26 The authors suggested that 2.5 ml of 0.5% isobaric levobupivacaine and 0.5% hyperbaric bupivacaine provided the same clinical outcomes for spinal anaesthesia.…”
Section: Discussionmentioning
confidence: 96%
“…[25 ] and Kokki et al [23 ] recently used levobupivacaine for performing spinal anaesthesia in neonates and children respectively. Levobupivacaine has been indicated to be safer than racemic bupivacaine because of the lower potential for cardiovascular and central-nervous-system toxicity, while maintaining similar properties and clinical efficacy.…”
Section: Drugs and Dosagesmentioning
confidence: 99%